BELGRADE MARKET AS A PART OF THE GLOBAL FINANCIAL MARKET - Simić, Nataša; Petrović, Vesna; Aničić, Dušan (Journal of process management and new technologies, 2018)
Belgrade market has been operating since 1989 under the name of Yugoslav capital market, which changed its name to Belgrade market in 1992. The purpose and the idea which governs our financial authorities and the market participants is a more active involvement of the market in the operations of the global financial market.